2015
DOI: 10.3139/146.111167
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of plastic deformation induced intermittent electromagnetic radiation characteristics with mechanical properties of Cu–Ni alloys

Abstract: This paper presents experimental results on intermittent electromagnetic radiation during plastic deformation of Cu -Nialloys under tension and compression modes of deformation. On the basis of the nature of electromagnetic radiation signals, oscillatory or exponential, results show that the compression increases the viscous coefficient of Cu -Ni alloys duringp lastic deformation. Increasingt he percentage of solute atoms in Cu -Nialloys makes electromagnetic radiation strength higher under tension. The electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A smooth correlation was observed between the EMR emission, grain size, and lattice constant [16,17]. Experiments using intermittent EMR in the plastic deformation of Cu-Ni alloys during tension and compression revealed that the compression viscosity coefficient increases during plastic deformation [18]. The plastic zone radius was correlated with the notch-depth ratio in tensile tests conducted on the Cu-Ni alloy [19].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A smooth correlation was observed between the EMR emission, grain size, and lattice constant [16,17]. Experiments using intermittent EMR in the plastic deformation of Cu-Ni alloys during tension and compression revealed that the compression viscosity coefficient increases during plastic deformation [18]. The plastic zone radius was correlated with the notch-depth ratio in tensile tests conducted on the Cu-Ni alloy [19].…”
Section: Introductionmentioning
confidence: 83%
“…Figure 3 shows the stress-strain plot depicting the stages of intermittent EMR emission for 2a/w = 0.33. The EMR signal for various metallic materials [13][14][15][16][17][18][19] exhibits exponential decaying and damped oscillating characteristics. Figure 4a shows the first EMR emission signal near yielding for 2a/w = 0.33, indicating an oscillating damping nature.…”
Section: Influence Of 2a/w On Emr Signal Characteristicsmentioning
confidence: 99%
“…Oskooie et al [14] studied the plastic deformation and strengthening mechanisms of an Al–Mg–Si alloy with a bimodal grain structure using optical microscope, transmission electron microscope and field emission scanning electron microscope equipped with an electron backscattered diffraction detector. Singh et al [15] presented experimental results on intermittent electromagnetic radiation during plastic deformation of Cu–Ni alloys under tension and compression modes of deformation. Rahman et al [16] studied the deformation behaviour of a twinning induced plasticity steel at quasi‐static strain rates using synchrotron X‐ray diffraction.…”
Section: Introductionmentioning
confidence: 99%